Introspekcia a kognitívna fenomenológia - Hvorecký, Juraj (Filosoﬁcký časopis, 2022)
In this article, the author presents the starting points for a discussion about cognitive phenomenality and, especially, the introspective arguments in its favor. These are based on the argument of abstracting away, in which we neglect its non-phenomenal parts from the selected cognitive state and the result of the operation is a pure phenomenal sense, associated with the cognitive state. The author describes the process of abstracting away with several examples. Immediately following other examples from the philosophy of emotions, he shows that in spite of its intuitive power, the method of abstracting away does not come with substantiated conclusions. This casts doubt on the strength of the introspective arguments that are raised in favor of cognitive phenomenology, especially in the context of a more general thesis about the unity of mind. Finally, the author comes to the conclusion that cognitive phenomenology needs other than introspective methods to defend itself.